ZINC, ITS FUNCTIONS AND ROLE IN THE IMMUNE SYSTEM - AKTAÇ, ŞULE (My University, 2020)
Zinc (Zn) is the essential mineral for the organism. It isa biological trace element that needs to be taken everyday for optimal health. Despite the vital necessity of Zn,the body has no warehouse that can be used to maintainmetal levels for a long time. Zinc is absorbed in the intestineby specific zinc-bearing proteins and distributedin the human body. Free zinc is rare in serum becausealbumin is highly attached on proteins such as α2-macroglobulin and transferrin. During zinc deficiency,while polymorpho nuclear cells chemotaxis and phagocytosisdecreased, zinc supplementation had the oppositeeffect. Pathogens are destroyed by the activity ofnicotinamide adenine dinucleotide phosphate (NADPH)oxidases which have been shown to be inhibited byboth zinc deficiency and excess after phagocytosis.

Çinko (Zn), organizma için temel minerallerden biridir._x000D_ Optimal sag lık için her gu n belirli bir miktarda alınması_x000D_ gereken bir eser elementtir. Hayati o neme sahip olan_x000D_ çinkonun vu cuttaki du zeyini korumak için kullanılabilecek_x000D_ bir çinko depose yoktur. Çinko, spesifik çinko_x000D_ taşıyan proteinler tarafından bag ırsakta emilir ve insane_x000D_ vu cudunda dag ıtılır. Serumda serbest çinko nadirdir;_x000D_ çu nku albu min, α2-makroglobulin ve transferrin gibi_x000D_ proteinlere bu yu k oranda bag lıdır. Çinko eksiklig inde_x000D_ polimorfo nu kleer hu creler kemotaksisi ve fagositoz_x000D_ azalırken, çinko takviyesi tam tersi bir etkiye sahiptir._x000D_ Patojenler, fagositoz sonrasında çinko yetersizlig i veya_x000D_ fazlalıg ı sonucu inhibe edildig i go sterilen nikotin amidadenin_x000D_ dinu kleotid fosfatoksidazlarının aktivitesi ile_x000D_ yok edilir.
ÇİNKO, FONKSİYONLARI VE İMMÜN SİSTEMDEKİ ROLÜ